Media Cards Line Up to Improve Primary School Students' Understanding of The Concept of Place Value - Cahyani, Widya Dwi; Riana Irawati; Cucun Sunaengsih (Program Studi Pendidikan Matematika Universitas Katolik Santo Agustinus Hippo, 2024)
Research to obtain information regarding increasing understanding of the concept of place value using Cards Line Up media in elementary schools. Using quantitative methods and a quasi-experimental nonequivalent control group design, involving two classes, namely the experimental class at SDN 1 Weru Lor and the control class at SDN 3 Weru Lor with a total of 30 students in each class. Data was collected using concept understanding tests in the form of descriptions, with analysis using gain analysis. The research results showed that there was a significant increase in students' conceptual understanding after being given treatment, as shown in the posttest results which were higher than the pretest results. This is confirmed by the N-Gain statistical test that there is a positive influence of Cards Line Up media on students' understanding with an increase of 0.47 which is classified as a moderate increase. With this, it can be summarized that the Cards Line Up media has proven to be able to increase students' understanding of the concept of place value material in elementary schools.